LB021-MON: The impact of a nutrition workshop on improving adherence to mediterranean diet and nutrition knowledge among adolescent swimmers - Philippou, Elena; Middleton, Nicos; Pistos, Constantinos M.; Andreou, Eleni; Petrou, Michael (My University, 2014)
Rationale: Adoption of healthy eating by adolescent athletes is imperative for normal growth as well as enhancing sport performance. The study aimed to examine the impact of a healthy eating workshop on adolescent swimmers’ dietary intake, nutrition knowledge and adherence to Mediterranean diet (MD). Methods: Healthy adolescent swimmers aged 13 19 y participated in a half-day educational workshop with emphasis on MD. Adherence to the MD was assessed using the KIDMED index at baseline and 6 weeks post-workshop. Additionally the following were assessed: blood biochemistry, anthropometrics, dietary practices and nutrition knowledge of food sources of macro- and micronutrients and MD definition. Results were analysed by paired t, Wilcoxon and McNemar’s tests as appropriate. Results are presented as mean ± standard deviation or median [interquartile range].Results: A total of 34 subjects participated (67.6% males, 76.5% normal weight and 23.5% overweight). Blood biochemistry was normal both pre- and post-intervention, while BMI was slightly reduced (21.5±2.1 vs 21.4±2.2; p < 0.01).Adherence to the MD was improved (poor: 14.7% vs 2.9%,medium: 64.7% vs 50.0%, good: 20.6% vs 47.1%; KIDMED score:5.00 [3.00] vs 7.00 [2.00]; p < 0.01). Nutrition knowledge also appeared improved (score: 7.00 [3.00] vs 7.00 [2.00]; p = 0.034). Participants reported eating more vegetables, olive oil, pulses and fish and less often in fast food stores (p < 0.05).Conclusion: The KIDMED index is an easy to use dietary assessment tool in this population group. A short educational workshop can improve adherence to MD and nutrition knowledge in adolescent swimmers with possible implications for their health.
Keywords: Nutrition; Mediterranean diet; Adolescent; Swimmers